Analysis of the Subgingival Microbiota in Implant-Supported Full-Arch Rehabilitations - Maria Menini; Francesca Delucchi; Francesco Bagnasco; Francesco Pera; Nicolò Di Tullio; Paolo Pesce (Dentistry Journal, 2020)
Background: The etiology of peri-implantitis is multifactorial, and it is not directly linked to the quantitative amount of plaque. The aim of this study was to evaluate the influence of subgingival microbiota around implants supporting full-arch restorations on clinical indexes of peri-implant health. Method: 47 patients (54 full-arch fixed rehabilitations) were included. Based on the highest value of probing depth (PD), 47 implants (in the test arch), 40 natural teeth and 7 implants (in the antagonist arch) were selected for microbiological sampling (traditional PCR and real-time PCR). Periodontal indexes (plaque index, PlI; probing depth, PD; bleeding on probing, BOP; peri-implant suppuration, PS) and marginal bone loss were also recorded. Results: Despite abundant plaque accumulation, the peri-implant parameters were within normal limits. No statistical difference was found in the microbial population around the test implants and antagonist natural teeth. Treponema denticola was present in a significantly higher amount around implants with increased PlI. Implants with increased BOP showed a significant increase in Treponema denticola and Tannerella forsythia. A significantly higher presence of Porphyromonas gingivalis, Treponema denticola and Tannerella forsythia was identified around the implants affected by peri-implantitis and in smokers. Conclusions: Peri-implantitis is characterized by a complex and polymicrobial disease, that might be influenced by the qualitative profile of plaque. Smoking might also favor implant biological complications in full-arch fixed prosthesis.